2014
DOI: 10.1007/s11065-014-9264-7
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Vascular Effects on Brain Injury and Cognition Late in Life: Knowns and Unknowns

Abstract: For some researchers, the relationship between prevalent cardiovascular risk factors and late-life cognitive decline is not worthy of further study. It is already known that effective treatment of vascular risk factors lowers risk of such major outcomes as stroke and heart attack, the argument goes; thus, any new information about the relationship between vascular risk factors and another major outcome - late-life cognitive decline-- is unlikely to have an impact on clinical practice. The purpose of this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 163 publications
(179 reference statements)
2
13
0
Order By: Relevance
“…First of all, confirming prior research [23,24,25], we found that obesity was related to a lower performance in verbal abilities, processing speed, and cognitive flexibility. This further corroborates the view that obesity is a major health-related antecedent of impairments in multiple domains of cognitive functioning such as memory, processing speed, and executive functioning in old age [20,21,22]. Furthermore, in line with prior evidence [6,14,15], we found that higher educational attainment, greater engagement in a broad variety of leisure activities, and higher cognitive level and lower physical demand of individuals' occupation were related to a better performance in all three investigated cognitive performance measures in old age.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…First of all, confirming prior research [23,24,25], we found that obesity was related to a lower performance in verbal abilities, processing speed, and cognitive flexibility. This further corroborates the view that obesity is a major health-related antecedent of impairments in multiple domains of cognitive functioning such as memory, processing speed, and executive functioning in old age [20,21,22]. Furthermore, in line with prior evidence [6,14,15], we found that higher educational attainment, greater engagement in a broad variety of leisure activities, and higher cognitive level and lower physical demand of individuals' occupation were related to a better performance in all three investigated cognitive performance measures in old age.…”
Section: Discussionsupporting
confidence: 83%
“…In general, obesity [body mass index (BMI) ≥30 [17]] is a major health risk, particularly in older adults. For instance, obesity is related to cardiovascular diseases and metabolic disorders such as diabetes [18,19], which are risk factors for cognitive impairment in old age [20,21,22]. In line with this, obesity has been found to be associated with impaired cognitive functioning such as memory and executive functioning in old age [23,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a critically low HDL-C level (<40 mg/dL) is related to an altered lipid metabolism, elevated lipid levels (including high plasma levels of low-density lipoprotein cholesterol [LDL-C] that are a marker of the transport of cholesterol from the liver to the cells via LDL particles), and therefore an increased risk for cardiovascular and cerebrovascular diseases [18,19,20]. Cardiovascular and cerebrovascular diseases in turn are a major risk factor for neurodegenerative disorders and cognitive impairment in old age [18,21]. These pathways explain that a critically low HDL-C level is related to lower cognitive functioning and faster cognitive decline (such as in memory) in old age [18,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The linkage of vascular risk factors (including stroke, heart attack, and diabetes) and late-life cognitive decline has been well established (Tuligenga 2015; Carmichael 2014; Knopman et al 2009) while that of heart failure and cognitive function has been unconfirmed (Cannon et al 2015). Plausible underlying mechanisms might be related to cerebral hypoperfusion or occult cerebrovascular disease, and it seems likely that these may coexist and exert synergistic effects.…”
Section: Discussionmentioning
confidence: 99%